Educational building of the Altai Branch of the RANEPA - Dering, Alexander; Zaitsev , Alexander; Kazarin, Evgeny (project baikal, 2024)
The article presents the history of the origin and development of the Altai Branch of the Russian Academy of National Economy and Public Administration (RANEPA) in Barnaul. It describes urban planning conditions and architectural principles of the construction of its new building and characterizes the features of the building.
Keywords: Barnaul; Altai Branch of RANEPA; metabolism; architecture